Sexually transmitted infection testing and self-reported diagnoses among a community sample of men who have sex with men, in Scotland. Issue 3 (5th October 2012) - McDaid, Lisa M; Li, Jessica; Knussen, Christina; Flowers, Paul
Abstract : Introduction: To examine sexually transmitted infection (STI) testing and self-reported diagnoses among men who have sex with men (MSM), in Scotland. Methods: Cross-sectional survey of seven Glasgow gay bars in July 2010 (n=822, 62% response rate); 693 are included in the analyses. Results: 81.8% reported ever having had an STI test; 37.4% had tested in the previous 6 months; 13.2% reported having an STI in the previous 12 months. The adjusted odds of having ever tested were significantly higher for men who had 6+ sexual partners in the previous 12 months (adjusted OR=2.66), a maximum sexual health knowledge score (2.23), and had talked to an outreach worker/participated in counselling (1.96), and lower for men reporting any high-risk unprotected anal intercourse (UAI) in the previous 12 months (0.51). Adjusted odds of recent testing were higher for men who had 6+ sexual partners (2.10), talked to an outreach worker/participated in counselling (1.66), maximum sexual health knowledge (1.59), and higher condom use knowledge (1.04), and lower for men aged ≥25 years (0.46). Adjusted odds of having had an STI in the previous 12 months were higher for men who had 6+ sexual partners (3.96) and any high-risk UAI in the previous 12 months (2.24) and lower for men aged ≥25 years (0.57). Conclusions: STI testing rates were relatively high, yet still below the minimum recommended for MSM at high risk. Consideration should be given to initiating recall systems for men who test positive for STIs, and to developing behavioural interventions which seek to address STI transmission.